2023
DOI: 10.1007/s00217-023-04283-0
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based comparison of the metabolome of beef from Simmental and black-and-white young bulls during wet- and dry-aging

Abstract: Taste as an eating quality factor of beef can be influenced by the selection of the raw material and aging method. The metabolic changes of different breeds during aging were analyzed in wet-aged and dry-aged beef up to 28 days of aging using samples from the M. longissimus thoracis et lumborum of the Simmental and Black-and-White breeds by 1H NMR spectroscopy. Breed affected the metabolome of beef samples before and during the aging of beef. The concentration of 24 of the 30 metabolites differed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(38 reference statements)
2
1
1
Order By: Relevance
“…This observation of the VIP scores was in accordance with the loadings of PC 2 values for the several buckets. These results were consistent with the literature (Cônsolo et al., 2021; Kim et al., 2020; Lee, Choe, et al., 2019) and our previous studies that highlighted isoleucine, leucine, and valine with high VIP scores (Bischof, Januschewski et al., 2023; Bischof, Witte, et al., 2023). Furthermore, the concentration of inosine 5′ monophosphate (IMP) decreased from 39% (DST) to 24% (WIP) and that of hypoxanthine (DST, 176%; WIP, 304%) increased with aging up to 28 days in all four different samples (Table S4).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This observation of the VIP scores was in accordance with the loadings of PC 2 values for the several buckets. These results were consistent with the literature (Cônsolo et al., 2021; Kim et al., 2020; Lee, Choe, et al., 2019) and our previous studies that highlighted isoleucine, leucine, and valine with high VIP scores (Bischof, Januschewski et al., 2023; Bischof, Witte, et al., 2023). Furthermore, the concentration of inosine 5′ monophosphate (IMP) decreased from 39% (DST) to 24% (WIP) and that of hypoxanthine (DST, 176%; WIP, 304%) increased with aging up to 28 days in all four different samples (Table S4).…”
Section: Resultssupporting
confidence: 93%
“…The levels of carnitine and creatine stagnated over aging time in DIP, WIP, and WST and levels of O ‐acetyl‐ l ‐carnitine stagnated in DIP and WIP. The same trends of changes in metabolite concentrations were observed in our previous studies in the wet matter of beef from different breeds, young bulls, cows, and heifers (Bischof, Januschewski, et al., 2023; Bischof, Witte, et al., 2023). In addition, the trends in concentration changes in amino acids and nucleotides were also found in the studies of Kim et al.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The decrease in carnosine and increase in L-carnitine with aging of the meat obtained in their study (Table 4) was not confirmed by Bischof et al [50] when examining non-aging and aging beef for 7 and 14 days. Carnosine content increased with aging of the beef, while L-carnitine remained at similar levels in both fresh and aged meat.…”
Section: Discussioncontrasting
confidence: 61%